Pengaruh Pembiayaan Murabahah dan Financing to Debt Ratio terhadap Profitabilitas yang dimoderasi oleh Non Performing Financing pada BTPN Syariah - Febrilyantri, Candra; Amah, Nik; Rizal, Fitra (Fakultas Syariah INSURI Ponorogo, 2023)
Murabahah financing is the most preferred financing option among customers due to its low risk and its versatility for working capital, consumption, or investment purposes. However, there is a phenomenon observed in BTPN Shariah where the increase in Murabahah financing is not accompanied by a rise in profits. Furthermore, the lack of profit increase is suspected to be due to the low Financing to Debt Ratio (FDR). This research aims to understand how Murabahah financing and FDR influence the profitability of Islamic banks, with Non-Performing Financing (NPF) acting as a moderator. The research sample includes quarterly reports from BTPN Shariah for the period 2015-2022, using purposive sampling techniques. The study utilizes SPSS 25 for analysis, including multiple linear regression,and Moderating Regression Analysis (MRA). The test results indicate that Murabahah financing, when considered individually, has an impact on profitability, whereas the Financing to Debt Ratio does not affect profitability. When both Murabahah financing and FDR are considered together, they collectively influence profitability with a percentage of 71.2% before moderation by NPF. The MRA results suggest that Non-Performing Financing is unable to moderate the impact of the two independent variables, namely Murabahah financing and FDR, on profitability.